A comprehensive comparison of the ICD-11 and DSM-5 section III personality disorder models - McCabe, Gillian A; Widiger, Thomas A (Psychological assessment, 2020)
The ICD-11 model of personality disorder consists of a level of severity, 5 trait domains, and a borderline pattern qualifier. Level of severity is assessed by the Standardized Assessment of Severity of Personality Disorder (SASPD; Olajide et al., 2018), the trait model by the Personality Inventory for ICD-11 (PiCD; Oltmanns & Widiger, 2018), and the borderline pattern qualifier by the Borderline Pattern Specifier inventory (BPS; Oltmanns & Widiger, 2019). The Section III Alternative Model of Personality Disorder includes a level of personality functioning and the five-domain trait model. These two components are assessed by the Level of Personality Functioning Scale (LPFS; Morey, 2017) and the Personality Inventory for (PID-5; Krueger, Derringer, Markon, Watson, & Skodol, 2012). Components of each model have been related to one another, but no study has yet considered all of the components for both models within one study. The current study considers the convergent, discriminant, and structural validity of the relationship of the LPFS and PID-5 with the SASPD, PiCD, and BPS. Also included were multiple measures of borderline personality disorder to determine if the BPS obtains incremental validity in accounting for borderline personality disorder variance above and beyond the trait models. (PsycINFO Database Record (c) 2019 APA, all rights reserved).